Fossil fuels, climate change, and the vital role of CO2 plays in thriving people and plants on planet earth - Ganapathy Shanmugam (Bulletin of the Mineral Research and Exploration)
A rigorous examination of empirical data confirms the fact that there is no threat from CO2 to People. Fossil Fuels (i.e., Oil, Natural Gas, and Coal) are the underpinning of modern living in the 21stcentury and that CO2 is essential for the thriving of both People and Plants. The geologic record shows that the Earth’s climate has always been changing naturally during the past 600 million yearsin terms CO2 and temperature, without CO2 emissions from Fossil Fuels by humans. A plot of CO2 vs. Temperature for the last 600 million years shows basically no correlation for most of thistime (Berner, 2004; Scotese et al., 2021). If the Net-Zero CO2 policy were to be implemented in 2050, large numbers of people would die and the modern human civilization would come to asudden halt, and humans left alive would have to revert back to the lifestyles of the Neanderthals. A climate-change model for 200 years (1900-2100) is proposed based on four basic parameters,namely, CO2, Temperature, Population, and GDP (gross domestic product) per capita. In this model, calculations based on the Max Planck’s Curve by Van Wijngaarden and Happer (2020), an increase in Temperature by 2100 would be trivial even if CO2 is nearly doubled in value to 800 ppm. The CO2 in the atmosphere helps not only to modulate the Earth’s Temperature suitable for human survival, but also to enhance Global Greening.